Case Report: An Unusual Case of Pulmonary Metastatic Adenocarcinoma From Low-Grade Appendiceal Mucinous Neoplasms - Zhao, Xin-Yu; Li, Chun-Qiang; Zhang, Shi-Yao; Liu, Gang (Frontiers in Oncology, 2022)
Background Low-grade appendiceal mucinous neoplasms (LAMNs) are indolent tumors with low-grade cytology. Although peritoneal dissemination is common due to tumor rupture and mucinous deposits on the visceral peritoneal surface, distant involvement, such as lung, is rarely seen due to lack of invasiveness. Case Presentation A 70-year-old woman presented to the hospital due to continuously elevated carcinoembryonic antigen (CEA) levels for 10 months without any symptoms. PET/CT revealed two lesions located in the left lung and appendix. The postoperative pathology results revealed pulmonary mucinous adenocarcinoma and LAMN. Then we performed next-generation sequencing (NGS) to clarify the relationship between the two tumors. The sequencing result showed that both tumors harbored the common tumor mutations, KRAS (p.G12D), GNAS (p.R201H), and BRAF (p.R735Q), which indicated that the pulmonary tumor was a metastasis of LAMN. Conclusion This case is unusual in that the primary LAMN and the pulmonary metastasis are present at the time of diagnosis. This study reported the first pulmonary metastasis from LAMN verified by NGS.